2020
DOI: 10.1007/s10803-020-04558-5
|View full text |Cite
|
Sign up to set email alerts
|

Digitally-Mediated Social Stories Support Children on the Autism Spectrum Adapting to a Change in a ‘Real-World’ Context

Abstract: Social Stories™ (SS) is a widely used intervention for children on the autism spectrum. A preliminary survey of 103 practitioners highlighted that SS are often used to support adapting to a change. This study investigated the use of digitallymediated SS to support ten children on the autism spectrum attending a school summer camp. Teacher perceptions of anxiety, understanding and closeness to the goal of the SS were assessed before and after the intervention (prior to the event). The pre-post-intervention comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 76 publications
6
17
0
11
Order By: Relevance
“…The findings are therefore consistent with previous studies, such as those carried out by Smith et al, [ 46 , 47 ] and by Constantin et al [ 32 ], who suggest that digitally-mediated SS could be effective in supporting children with autism. This could be achieved by utilising digital-mediation to maximise procedural integrity by improving an “author’s” competence to develop and deliver a SS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings are therefore consistent with previous studies, such as those carried out by Smith et al, [ 46 , 47 ] and by Constantin et al [ 32 ], who suggest that digitally-mediated SS could be effective in supporting children with autism. This could be achieved by utilising digital-mediation to maximise procedural integrity by improving an “author’s” competence to develop and deliver a SS.…”
Section: Discussionsupporting
confidence: 92%
“…Those with the least levels of competence and positive attitudes, perceived the greatest improvement in their competence and positive attitudes. The findings are therefore consistent with previous research which indicates that digitally mediated social stories can reduce the variability in the development of the stories and the delivery of the intervention, and improve effectiveness [ 43 , 46 , 47 ]. This study suggests that this may extend to parents and practitioners with a wide range of levels of previous experience.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They reported that support through the use of digital-mediation (where SSs were developed using an online application and delivered through a smart-phone or tablet) resulted in greater fidelity and subsequent positive outcomes in terms of "closeness to a goal" of the SS. Similar studies by Smith et al (2020b) and Hanrahan et al (2020) also produced similar conclusions: that digitally-mediated social stories were effective in producing beneficial changes in behaviour outcomes whilst also improving procedural integrity. For example, Hanrahan et al (2020) reported an increase in the intensity of a child's interaction with the content of the story as a result of using technology, which in turn led to better engagement and increased comprehension.…”
Section: Introductionsupporting
confidence: 53%